Analisa Pengganda dan Distribusi Keuntungan Perdagangan di Wilayah ASEAN - Parewangi, A. M. Alfian; Brodjonegoro, Bambang P. S. (UI Scholars Hub, 2003)
Matrices of lnternational Trade model shows world equilibrium and the inter-linkage among countries through trade. This approach enable us to decompose trade multiplier into direct import requirement, indirect import requirement, internal and external propagation as components of total trade multiplier. We also can run growth simulation to identify the distribution of trade gain as previously applied by Miyazawa, Hewings and other authors. Using trade flow data from 178 countries, and focusing on the big five ASEAN, we conform the most important role of Singapore and Malaysia in this region. We also find the role of United States and Japan as biggest and most important trading partner. Unsurprisingly, growth simulation shows unequal trade gain distribution between ASEAN countries and their trading partner.